Androgen hormone levels in women with male pattern baldness - Martinović, Nevenka (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
Backgraund. Adrogen hormones in women with androgenetic alopecia (AA) were studied. Materials and methods. The prospective study included 50 women with adrogenetic alopecia in fertile age. Blood and urine were taken on the 7th and21st day of the same menstrual cycle. Free testosterone (T), androstanediole (A-DIOL) and dehy droepiandrosterone (DHA) were assayed in serum. In the 24-hour urine T, DHA, androsterone (A), etiocholanolone (E) and 17-ketosteroid (17-KS) levels were monitored. Results. Statistical deviation from physiological levels was observed for serum T. Conclusion. It is suggested that A-DIOL was possibly the principal androgen in etiopathogenesis of AA in women. The hormonal disorder seems to be expressed in the estrogen phase of the menstrual cycle.
Keywords: 17-ketosteroids; Alopecia; Androstenedione; Androsterone; Blood; Etiocholanolone; Physiopathology; Prasterone; Testosterone; Urine